The economic impact of COVID-19 from a global perspective - Alam Khan; Nadeem Khan; Muhammad Shafiq (Contemporary Economics, 2021)
The world has been waging a fight against the novel coronavirus (COVID-19) since December 2019. The current coronavirus crisis is a catastrophe affecting billions of families worldwide. So far, COVID-19 has wreaked havoc across the globe: by slowing down economic growth; decreasing global trade; hurting health sector; increasing unemployment and underemployment; reducing FDI and hurting the tourism sector. This study investigates the economic costs of COVID-19. By using descriptive analysis, this study shows that the major economic variables, such as economic growth, global trade, health sector, unemployment and underemployment, foreign direct investment and travel and tourism sector have significantly affected by COVID-19.
Keywords: R11; 330; COVID-19; economic performance; global economy